Pengaruh Stres Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT Jaya Kencana Divisi Lift Eskalator Proyek (LEP) - Faraditya Ayudiantina (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Employee performance is an important factor in achieving organizational goals and is influenced by various factors, including work stress and the work environment. This study aims to analyze the effect of work stress and the work environment on employee performance at PT Jaya Kencana Lift Escalator Project Division (LEP). This research employed a quantitative approach using questionnaire-based data collection. The population consisted of 152 employees, with a sample of 110 respondents selected using the Slovin formula and Probability Sampling through the Simple Random Sampling technique. Data were analyzed using IBM SPSS Statistics 26 through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis. The results showed that partially, work stress had no significant effect on employee performance with a t-value of 1.324 and a significance value of 0.188 (>0.05). Meanwhile, the work environment had a positive and significant effect on employee performance with a t-value of 3.504 and a significance value of 0.001 (<0.05). Simultaneously, work stress and the work environment significantly affected employee performance with an F-value of 6.939 and a significance value of 0.001 (<0.05). The R Square value of 0.386 indicates that both independent variables explained 38.6% of the variation in employee performance, while the remaining 61.4% was influenced by other factors outside this study.